Embryonic canalization and its limits—A view from temperature. Issue 2 (3rd February 2020) - Irvine, Steven Q.
Abstract: Many animals are able to produce similar offspring over a range of environmental conditions. This property of the developmental process has been termed canalization—the channeling of developmental pathways to generate a stable outcome despite varying conditions. Temperature is one environmental parameter that has fundamental effects on cell physiology and biochemistry, yet developmental programs generally result in a stable phenotype under a range of temperatures. On the other hand, there are typically upper and lower temperature limits beyond which the developmental program is unable to produce normal offspring. This review summarizes data on how development is affected by temperature, particularly high temperature, in various animal species. It also brings together information on potential cell biological and developmental genetic factors that may be responsible for developmental stability in varying temperatures, and likely critical mechanisms that break down at high temperature. Also reviewed are possible means for studying temperature effects on embryogenesis and how to determine which factors are most critical at the high‐temperature limits for normal development. Increased knowledge of these critical factors will point to the targets of selection under climate change, and more generally, how developmental robustness in varying environments is maintained. Abstract : Environmental influences on development and mechanisms fostering robustness/canalization of the embryonic phenotype. Research Highlights: Animal developmental programs have mechanisms for compensating for environmental variation, resulting in canalized phenotypes over a range of temperatures. This review examines those mechanisms and their limits, and how they might be further studied.